On convergence and asymptotic behaviour of semigroups of operators. (27th November 2020) - Bobrowski, Adam; Rudnicki, Ryszard
Abstract : The classical and modern theorems on convergence, approximation and asymptotic stability of semigroups of operators are presented, and their applications to recent biological models are discussed. This article is part of the theme issue 'Semigroup applications everywhere'.